The Need for a Comprehensive Competency-Based Career Guidance Curriculum for Teen Mothers - Mary-Beth Muskin (Educational Considerations, 2004)
Teen parenting has significant implications for teens and their success in school. As school guidance and counseling departments focus on the development of comprehensive competency-based guidance curriculum within their school systems, the needs of teen parents are often overlooked.